Prevalence, genotyping, and molecular relatedness of methicillin-resistant Staphylococcus aureus isolated from tertiary care hospitals in Jeddah, Saudi Arabia: MRSA prevalence and genetic analysis in Jeddah Hospitals - Dawoud, Turki M.; A. Al-Hajjaj, Yasser; Mubarak, Ayman; Elbehiry, Ayman; El-Tayeb , Mohamed; Moussa, Ihab Mohamed (Cellular and Molecular Biology, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen causing severe morbidity and mortality in hospitals globally.Transmission of MRSA occurs within the healthcare sector as a nosocomial infection, primarily facilitated by healthcare workers or patients admitted to medical facilities. The objective of this study was to evaluate the genetic characterization and similarity of MRSA strains isolated from both inpatients and outpatients who visited various healthcare facilities in Jeddah, Saudi Arabia. A total of 200 MRSA strains were isolated from participants between March 2018 and June 2019. The recovered strains were characterized using both phenotypic and genotypic methods. All isolates (n=200) tested positive for the S. aureus 16S rRNA gene, with 92.5% also testing positive for the mecA gene, while 7.5% were identified as methicillin-susceptible. Furthermore, the typing and subtyping of the staphylococcal cassette chromosome mec (SCCmec) genetic element indicated that 61.6% of the MRSA strains were classified as type III (hospital-acquired), while 32.4% were identified as type IV and 6% remained of an unknown type. Subtyping of SCCmec type IV and the detection of the Panton-Valentine leukocidin (PVL) gene were also conducted. The genetic relatedness among MRSA isolates, assessed through Random Amplified Polymorphic DNA Polymerase Chain Reaction (RAPD-PCR), revealed two primary clusters, with no discernible differentiation between outpatient and inpatient strains. Additionally, Pulsed-Field Gel Electrophoresis (PFGE) fingerprinting of the examined strains identified four major clusters. The first cluster comprised three groups (16 strains), isolated from patients with respiratory and soft tissue infections. The second cluster included two groups (12 strains), all recovered from patients with respiratory, soft tissue, and urinary tract infections (UTIs). The third and fourth clusters each contained one group (6 strains and 5 strains, respectively), all isolated from outpatients. In conclusion, Antimicrobial susceptibility testing showed significant resistance to ceftriaxone, ampicillin, and amoxicillin-clavulanic acid, with vancomycin and gentamicin being the most susceptible. Multiplex PCR identified all positive MRSA strains within hours. Most isolates were SCCmec type III and type IV. The PVL gene was found in all S. aureus isolates, especially in type IV and methicillin-sensitive strains, but not in type III. RAPD-PCR analysis revealed distinct profiles for outpatient and inpatient strains.